A Complex Puzzle : Realities of English-speaking Seniors in Quebec - Bell, Shannon (Quebec English-speaking Communities Research Network (QUESCREN), 2025)
Ideally, we would grow old in good health, maintaining physical and mental well-being and enjoy social inclusion and economic security in a respectful and supportive environment. However, despite strategies to build toward such an ideal in the face of an aging population, public policy and programs at all levels of government largely continue to be shaped by the needs of younger generations. This brief looks at challenges that Quebec’s English-speaking seniors face. It draws on research and policy efforts aimed at understanding and improving the aging experience in the province.

Accès aux services de santé et aux services sociaux pour les communautés anglophones en situation minoritaire du Québec : Défis récents, contexte législatif et recommandations de recherche - Shoumarova, Lina (Quebec English-speaking Communities Research Network (QUESCREN), 2024)
Le présent mémoire offre des observations préliminaires sur les recherches existantes concernant l’accès aux services de santé et sociaux pour la communauté anglophone de langue officielle en situation minoritaire au Québec. Il identifie des thèmes et des besoins de recherche. Le mémoire fait également une recommandation sur des mesures qui renforceraient l’écosystème de recherche et soutiendraient ainsi les travaux dans le domaine. Ce mémoire répond donc à la priorité G – « le besoin de recherche, de preuves et de solutions pour soutenir l’accès aux soins de santé dans la langue choisie » – décrite dans le document préparatoire de l’étude du Comité permanent mentionnée ci-dessus
Keywords: Official Language Minority Community (OLMC)

Access to Health and Social Services for Quebec’s English-Speaking Minority Communities: Recent Challenges, Legislative Context, and Research Recommendations - Shoumarova, Lina (Quebec English-Speaking Communities Research Network (QUESCREN), 2024)
This brief offers preliminary observations about existing research on access to health and social services for Quebec’s English-speaking official language minority community (OLMC). It identifies research themes and needs. The brief also makes a recommendation for measures that would strengthen the research ecosystem and thus support work in the field. As such, this brief addresses Priority G – “the need for research, evidence, and solutions to support health care access in one’s chosen language” – outlined in the preparatory document for the Standing Committee’s study mentioned above.
Keywords: Official Language Minority Community (OLMC)

Access to Health and Social Services for Quebec’s English-speaking Minority Communities: Recent Challenges, Legislative Context, and Research Recommendations - Shoumarova, Lina (Quebec English-speaking Communities Research Network (QUESCREN), 2024)
This brief offers preliminary observations about existing research on access to health and social services for Quebec’s English-speaking official language minority community (OLMC). It identifies research themes and needs. The brief also makes a recommendation for measures that would strengthen the research ecosystem and thus support work in the field. As such, this brief addresses Priority G – “the need for research, evidence, and solutions to support health care access in one’s chosen language” – outlined in the preparatory document for the Standing Committee’s study mentioned above.

Le QCGN se dit heureux de l’adoption de la motion visant à supprimer le certificat d’identité permettant d’avoir accès aux soins de santé - Quebec Community Groups Network (QCGN) (2024)

QCGN Pleased by Motion To Nix Identity Certificate for Health Care - Quebec Community Groups Network (QCGN) (2024)

Le risque de suicide pour la population québécoise d'expression anglaise - Community Health and Social Services Network (CHSSN) (2024)

Suicide Risk for Quebec’s English-speaking Population - Community Health and Social Services Network (CHSSN) (2024)

Adaptation Initiative Project Guide : 2023-2028 - Community Health and Social Services Network (CHSSN) (2024)
This guide to the CHSSN Adaptation Projects 2023– 2028 gives the descriptions of the projects being carried out by our public partners to improve access to health services across the province. These projects take into account the diverse regional realities of the English-speaking communities and are designed to have a direct impact on the ability of an Englishspeaking client to access services in English. Each region develops a project that will advance their capacities to understand the needs of the community and better respond to them. The primary objectives of this program are to 1) improve access to health and social services in English in all regions and 2) support better communication and partnerships between the English-speaking community and public health establishments.

L'initiative d'adaptation guide de projets : 2023-2028 - Community Health and Social Services Network (CHSSN) (2024)
Le présent guide des projets d’adaptation 2023 – 2028 du Réseau communautaire de santé et de services sociaux (RCSSS/ CHSSN) décrit les projets menés par nos partenaires publics en ce qui concerne l’amélioration de l’accès aux services de santé partout dans la province. Ces projets tiennent compte des différentes réalités régionales des communautés d’expression anglaise et sont pensés de façon à avoir un effet direct sur l’accès aux services en anglais pour la clientèle d’expression anglaise. Chaque région élabore son propre projet pour mieux comprendre les besoins de la communauté et mieux y répondre. Les objectifs principaux du programme sont 1) d’améliorer l’accès aux services de santé et aux services sociaux en anglais dans toutes les régions et 2) de cultiver une meilleure communication et de bons partenariats entre la communauté d’expression anglaise et les établissements de santé publique.

L'accès en anglais aux services de santé et aux services sociaux au Québec : Rapport comparatif 2019-2023 - CROP (2024)

English-language Health and Social Services Access in Québec : Comparison 2019-2023 - CROP (2024)

Brief for Consultations with the Secrétariat aux relations avec les Québécois d’expression anglaise - Seniors Action Quebec (SAQ) (2024)

Communauté du CHSSN Netlink - Community Health and Social Services Network (CHSSN) (2024)

Community Netlink - Community Health and Social Services Network (CHSSN) (2024)

Pregnancy Outcomes in Anglophone Quebec : Recent Research Results - Auger, Nathalie (QUESCREN Lunch & Learn, 2023)

Déclaration du QCGN concernant le projet de loi 15 et le recours au bâillon - Quebec Community Groups Network (QCGN) (2023)

QCGN Statement on Bill 15 and Closure - Quebec Community Groups Network (QCGN) (2023)

Brief to the Senate Standing Committee on Official Language’s Study of Matters Relating to Minority-language Health Services - Quebec Community Groups Network (QCGN) (2023)

Seniors Action Quebec Presentation on Study Matters Relating to Minority-Language Health Services - Seniors Action Quebec (SAQ) (2023)

English-language Health and Social Services Access in Québec - Community Health and Social Services Network (CHSSN) (2023)

Seniors Action Quebec Brief : Vieillir et vivre ensemble, chez soi, dans sa communauté, au Québec (VVE) - Plan d’action 2024-2029 - Seniors Action Quebec (SAQ) (2023)

Access to Justice in English Project : Senior Care Services in English in Quebec : Executive Summary of Final Report and Recommendations to the Ministry of Health and Social Services - Quebec Community Groups Network (QCGN) (2023)

Make the Case Report : Access to Senior Care in English in Quebec : A research analysis of English language rights in Quebec health care and access to the SAPA program for English-speaking seniors in Quebec - Quebec Community Groups Network (QCGN) (2023)
This report discusses and details one of the AJEQ Project’s candidate issues of research: access to senior health care services in English in Quebec’s SAPA program (Soutien à l’autonomie des personnes âgées). The issue was selected on the basis of prior research conducted by the AJEQ Project, including a population survey of 1,601 English-speaking Quebecers conducted by Quorus Consulting Group in September 2021, which revealed that hospitals and CLSC care were among the most widely accessed provincial government services by English-speaking Quebecers, and that more than one in three English-speaking Quebecers who had accessed these services in the past two years found it difficult to do so in English. The issue of senior care was under close scrutiny at the time the issue was selected, in the wake of the COVID-19 pandemic and the subsequent coroner’s inquiry into pandemic-related deaths at seniors’ residences across Quebec.

Projet Accès à la justice en anglais : Services de soins aux personnes âgées en anglais au Québec : Sommaire du rapport final et recommandations au Ministère de la Santé et des Services sociaux - Quebec Community Groups Network (QCGN) (2023)

Access to Justice in English Project : Senior Care Services in English in Quebec - Quebec Community Groups Network (QCGN) (2023)
QCGN’s Access to Justice in English Project (“the AJEQ Project”) identifies and researches areas where the English-speaking community are experiencing difficulty accessing their rights, with a strong focus on community access to public services. It leverages information as a strategic resource to understand and improve access to justice in English in Quebec. The second issue studied by the Project was access to health care services for seniors in English through Quebec’s SAPA program (Soutien à l’autonomie des personnes âgées). The issue was selected on the basis of prior research conducted by the AJEQ Project, including a population survey of 1,601 English-speaking Quebecers conducted by Quorus Consulting Group in September 2021, which revealed that hospitals and CLSC care were among the most widely accessed provincial government services by English-speaking Quebecers, and that more than one in three English-speaking Quebecers who had accessed these services in the past two years found it difficult to do so in English. The issue of senior care was under close scrutiny at the time the issue was selected, in the wake of the COVID-19 pandemic and the subsequent coroner’s inquiry into pandemic-related deaths at seniors’ residences across Quebec.

Senior Care Services in English in Quebec : Executive Summary of Final Report and Recommendations of the Ministry of Health and Social Services - Quebec Community Groups Network (QCGN) (2023)
QCGN’s Access to Justice in English Project (“the AJEQ Project”) identifies and researches areas where the English-speaking community are experiencing difficulty accessing their rights, with a strong focus on community access to public services. It leverages information as a strategic resource to understand and improve access to justice in English in Quebec. The second issue studied by the Project was access to health care services for seniors in English through Quebec’s SAPA program (Soutien à l’autonomie des personnes âgées). The issue was selected on the basis of prior research conducted by the AJEQ Project, including a population survey of 1,601 English-speaking Quebecers conducted by Quorus Consulting Group in September 2021, which revealed that hospitals and CLSC care were among the most widely accessed provincial government services by English-speaking Quebecers, and that more than one in three English-speaking Quebecers who had accessed these services in the past two years found it difficult to do so in English. The issue of senior care was under close scrutiny at the time the issue was selected, in the wake of the COVID-19 pandemic and the subsequent coroner’s inquiry into pandemic-related deaths at seniors’ residences across Quebec.

Impact Report 2022-2023 - 4Korners (2023)

Committee for Anglophone Social Action Annual Report - Committee for Anglophone Social Action (CASA) (2023)

Annual Report 2022-2023 - Community Health and Social Services Network (CHSSN) (2023)

CHSSN À propos de Nous / Who We Are - Community Health and Social Services Network (CHSSN) (2023)
Through a program called the Networking and Partnership Initiative (NPI), the CHSSN supports 23 community organizations serving English-speaking communities across the province in their efforts to collaborate with partners to improve access to health and social services in English (see map).

CHSSN Senior Wellness Centre Initiative Activity Report Year 2 (2022-2023) - Community Health and Social Services Network (CHSSN) (2023)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2023)

Community NetLink - Community Health and Social Services Network (CHSSN) (2023)

Investing in the Vitality of English-speaking Quebec / Investir dans la vitalité du Québec d'expression anglaise - Community Health and Social Services Network (CHSSN) (2023)
Keywords: Official Language Minority Community (OLMC)

Networking and Partnership Initiative / Initiative de réseautage et de partenariat (NPI) - Community Health and Social Services Network (CHSSN) (2023)

Senior Wellness Centre Initiative Activity Report (2022-2023) - Community Health and Social Services Network (CHSSN) (2023)

Annual Report 2022-2023 - English Speaking Catholic Council (2023)

2023 Report : "An Analysis of the Demographic and Socio-Economic Characteristics of Quebec's English-Speaking Community Compared to the French-Speaking Population" with a Focus on the RTS de la Montérégie-Oues - Montérégie West Community Network (MWCN) (2023)

Explorer les effets de la langue comme obstacle à l’accès aux soins, à l’utilisation des services et au bien-être pour les familles anglophones du Québec - McGill Department of Educational and Counselling Psychology; CareLab (2022)
La langue a été nommée comme obstacle à l’accès et à l’utilisation des soins de santé pour les anglophones du Québec et pour une multitude d’autres minorités linguistiques partout dans le monde. Plus précisément, ces obstacles se manifestent par la difficulté d’accéder à un professionnel de la santé, par exemple pour prendre un rendez-vous dans la langue de son choix, le manque de choix quant aux traitements et services nécessaires, la difficulté à comprendre le plan de traitement et les résultats d’examens et le manque de services dans la langue de son choix lorsqu’on est orienté vers un spécialiste de la santé.

Consensus on Language Issues in Quebec - Quebec Community Groups Network (QCGN); Association for Canadian Studies (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Partners in Health - Centre for Access to Services in English (CASE) (2022)

2018–2021 Health and Social Services Bursary Program Portrait - Dialogue McGill (2022)
Created by Dialogue McGill in 2011 as a retention initiative, the Health and Social Services Bursary Program provides bursaries to students pursuing studies in health care and psychosocial services who have committed to practice in their field in their home region upon completion of their studies. The bursaries are coordinated locally by the English- speaking Community Networks in different Quebec regions and are designed to respond to regional and local priorities for access to services in English by retention of these graduates in their region of origin.

Le modèle de liaison communautaire : Améliorer l'accès aux services de santé et aux services sociaux pour les communautés d'expression anglaise du Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2022)
Ce rapport explore le rôle du travail de liaison communautaire dans l'amélioration de la santé et du bien-être des personnes et des communautés qui font face à des obstacles dans leur accès aux services de santé publics. Il s'intéresse plus particulièrement au modèle de liaison du CHSSN, qui constitue une réponse communautaire prometteuse pour réduire les obstacles linguistiques et culturels auxquels se heurtent les communautés d’expression anglaise du Québec.
Keywords: Official Language Minority Community (OLMC)

The Community Liaison Model : Improving Access to Health and Social Services to Quebec's English-speaking Communities - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2022)
This report explores the role of community liaison work in improving the health and wellbeing of individuals and communities who face barriers in their access to public healthcare services. Of specific focus is the CHSSN liaison model as a promising community-based response to reducing the linguistic and cultural barriers experienced by Quebec’s Englishspeaking communities.
Keywords: Official Language Minority Community (OLMC)

Understanding the Long-term Care Experience of Official Language Minorities in Canada: An Environmental Scan - Hsu, Amy T.; Ménard, Alixe; Scott, Mary (2022)
Members of minority and racialized communities across Canada commonly experience disparities in health and healthcare. In the context of the COVID-19 pandemic, minority and racialized individuals have been found to report poorer health outcomes and added barriers to healthcare access. While there is growing understanding of the impact of COVID-19 on individuals who live and work in residential long-term care (LTC) homes and other congregate care settings, little attention has been directed at examining inequities in the care experience and care-related outcomes that equity-seeking groups, including Official Language Minority Communities (OLMC), face within LTC. It’s clear that there is a need for systemic change within LTC; the pandemic, especially in its first two waves, highlighted several pre-existing issues within this sector. To ensure high-quality and equitable care for all aging Canadians, these system-level changes must be informed by evidence.
Keywords: Official Language Minority Community (OLMC)

Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada : état des lieux - Hsu, Dre. Amy T; Ménard, Alixe; Scott, Mary (2022)
Les membres des communautés racisées et en situation minoritaire du Canada vivent souvent des disparités en matière de santé et de soins de santé. Dans le contexte de la pandémie de COVID-19, on a constaté que les personnes membres d’une minorité et les personnes racisées signalaient de moins bons résultats de santé et des barrières supplémentaires à l’accès aux soins de santé. Bien que l’on comprenne de plus en plus l’incidence de la COVID-19 sur les personnes vivant et travaillant dans des établissements de soins de longue durée (SLD) et dans d’autres établissements de soins collectifs, on a porté peu d’attention à l’examen des inégalités dans l’expérience des soins et des résultats liés aux soins auxquels font face les groupes en quête d’équité, y compris les communautés de langue officielle en situation minoritaire (CLOSM). Il est clair qu’il faut apporter des changements systémiques au sein du secteur des SLD; la pandémie, surtout au cours de ses deux premières vagues, a mis en lumière plusieurs problèmes préexistants dans ce secteur. Pour assurer des soins de grande qualité et équitables pour tous les Canadien(ne)s âgés, ces changements au niveau du système doivent être fondés sur des données probantes.
Keywords: Official Language Minority Community (OLMC)

Committee Examines Obligations of Professionals to Provide Documentation in French - Quebec Community Groups Network (QCGN) (2022)

La commission examine l’obligation des professionnels de fournir leur documentation en français - Quebec Community Groups Network (QCGN) (2022)

Quietly Adopted Regulation Could Hurt Quality of Health Care for English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2022)

Un réglement adopté en catimini pourrait nuire à la qualité des soins de santé des Québécois d'expression anglaise - Quebec Community Groups Network (QCGN) (2022)

Améliorer la santé et le bien-être des aînés d’expression anglaise vivants dans les Laurentides au Québec - Helou, Rola; Finch, Lois; Richardson, Mary (4Korners, 2022)
La présente évaluation des besoins a été réalisée à la demande du Réseau communautaire des Laurentides 4Korners, un organisme caritatif canadien enregistré qui a été fondé en 2005 dans le but de faire connaître aux citoyens des Laurentides les programmes et les services qui répondent à leurs besoins dans un environnement sécuritaire et inclusif. Elle a pour objectif de déterminer les besoins de la population âgée d’expression anglaise des Laurentides et de vérifier si ces besoins sont présentement satisfaits. Cette évaluation a été menée par le Conseil scolaire des Premières Nations en éducation des adultes, en collaboration avec la firme de consultants S.O.A.R. Solutions. Les travaux ont été réalisés sous la supervision du Comité d’évaluation des besoins des aînés (SNAC), lequel est composé de membres du personnel de 4Korners, du Elders’ Community Worker du Centre de santé Kanesatake, de bénévoles et de consultants en projets du Conseil scolaire des Premières Nations en éducation des adultes.

Improving the Health and Well-being of English-speaking Seniors in the Laurentians, Québec : A Needs Assessment - Helou, Rola; Finch, Lois; Richardson, Mary (4Korners, 2022)
This needs assessment was commissioned by the 4Korners Laurentian Community Network, a registered Canadian charitable organization founded in 2005, which connects individuals of the Laurentians with programs and services to meet their needs in a secure and inclusive environment. The objective was to identify the needs of the aging English-speaking population in the Laurentians and to determine if they are currently being met. The First Nations Adult Education School Council conducted the assessment in partnership with S.O.A.R. Solutions, a consulting firm. The work was overseen by a committee (the Seniors’ Needs Assessment Committee, SNAC), made up of 4Korners employees, volunteers, the Elders’ Community Worker from the Kanesatake Health Center and project consultants from the First Nations Adult Education School Council.

CHSSN Community Netlink - Community Health and Social Services Network (CHSSN) (2022)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2022)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2022)

Community NetLink - Community Health and Social Services Network (CHSSN) (2022)

Sondage Youth Pulse Check : Principales conclusions - Community Health and Social Services Network (CHSSN) (2022)

Youth Pulse Check Survey : Key Findings - Community Health and Social Services Network (CHSSN) (2022)

Lunch & Learn : Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada: un état des lieux / Understanding the Long-Term Care Experience of Official Language Minorities in Canada : An Environmental Scan - Ménard, Alixe; Scott, Mary; Hsu, Amy (2022)

Sondage Youth Pulse Check : Rapport des résultats du sondage - Nigam, Sunita (Community Health and Social Services Network (CHSSN), 2022)
This document outlines the most important findings of the Youth Pulse Check, a mental health survey filled out by 456 English-speaking youth between the ages of 18-29 from 14 regions across the province of Quebec. Although 90% of respondents said they struggled at least somewhat often with their mental wellbeing and 81% of respondents, said that the COVID-19 pandemic has increased their struggles to feel well at a level 3 or more on a scale of 1 to 5, the survey revealed that many English-speaking youth feel there are significant gaps and barriers in accessing mental health services in their region. If many youth reported having sought out help in the past without success—meeting with barriers such as long wait lists, the prohibitive costs of mental health support, or the unavailability of services in English— other youth reported not having sought out help because of a lack of information about services to which they might turn.

Youth Pulse Check : Survey Results Report - Nigam, Sunita (Community Health and Social Services Network (CHSSN), 2022)
This document outlines the most important findings of the Youth Pulse Check, a mental health survey filled out by 456 English-speaking youth between the ages of 18-29 from 14 regions across the province of Quebec. Although 90% of respondents said they struggled at least somewhat often with their mental wellbeing and 81% of respondents, said that the COVID-19 pandemic has increased their struggles to feel well at a level 3 or more on a scale of 1 to 5, the survey revealed that many English-speaking youth feel there are significant gaps and barriers in accessing mental health services in their region. If many youth reported having sought out help in the past without success—meeting with barriers such as long wait lists, the prohibitive costs of mental health support, or the unavailability of services in English— other youth reported not having sought out help because of a lack of information about services to which they might turn.

English : an Asset! - Réseau de l’est de l’île pour les services en anglais (REISA) (2022)

Partners in Health - Centre for Access to Services in English (CASE) (2021)

The Importance of Resurrecting English-speaking Healthcare Services in Québec - Jackson-Cappuccino, Ella (Youth for Youth Québec (Y4Y Québec), 2021)
French is the first language of 71.2% of Quebecers. For the remaining 27.9%, communication outside of this language can be difficult, especially in regard to health care (Ouimet et. al 3).This is of concern as those who seek medical attention or health resources may not be provided adequate care given the linguistic barrier. Particularly, it is Québec’s Englishspeaking minority that is most affected by this issue (Ouimet et. al 3). Within this minority, there are still hundreds of thousands of English-speaking individuals who desire to seek health services in their first official language. The wish does not simply arise due to a lack of bilingualism. Evidence shows that in times of crisis - when individuals look to communicate a matter of importance - they most often revert to their mother tongue (Silver 686). Without resources designed to cater to the English-speaking population, the government subjects this linguistic minority group to unequal health care services.

Partners in Health - Centre for Access to Services in English (CASE) (2021)

Réduction des services dans les CLSC de la Basse-Côte-Nord - Buffitt, Kimberly (2021)

Reduction in Services at the CLSC's on the Lower North Shore - Buffitt, Kimberly (2021)

Network News - Quebec Community Groups Network (QCGN) (2021)

Partners in Health - Centre for Access to Services in English (CASE) (2021)

Partners in Health - Centre for Access to Services in English (CASE) (2021)

Establishing a Community Task Force on Mental Health : Exploring the Role of Minority Language Communities in Improving Access to Mental Health Services - Mental Health & Wellness Gaspésie (2021)
Keywords: Official Language Minority Community (OLMC)

Evaluation of the Quebec Community Health and Social Service Foundation's (QCHF) Patient Navigator Project - Anastasopoulos, Vanessa (2021)

CHSSN Survey to Access to English-language Health and Social Services - Community Health and Social Services Network (CHSSN) (Building Together, 2021)

How Services Can Better Address the Realities of English-Speaking Fathers - Community Health and Social Services Network (CHSSN) (2021)
A report based on an analysis of recent surveys and public data, identified five essential ways family services can better address the realities of English-speaking fathers.

2021 Virtual Conference : Addressing Access to Health Care and Social Services for Language Minorities : Best Practices and Latest Evidence - Dialogue McGill (2021)

Conférence virtuelle 2021 : Accès aux soins de santé et aux services sociaux pour les minorités linguistiques : pratiques exemplaires et les résultats probants - Dialogue McGill (2021)

Understanding the Experience of English-speaking Seniors in Quebec : Accessing and Interacting with Health and Social Services and the Effect on Health Outcomes - Recreo Therapy (Community Health and Social Services Network (CHSSN), 2021)

Building Bridges : Final Report on the 2019 Consultations : 2019 Consultation with Organizations Serving English-speaking Communities on the Priorities and Orientations of the Secrétariat aux relations avec les Québécois d'expression anglaise - Ravensbergen, Frances (Secrétariat aux relations avec les Québécois d’expression anglaise (SRQEA), 2020)
In the fall of 2019, the Secrétariat aux relations avec les Québécois d’expression anglaise (the “Secrétariat”) consulted with its community and institutional stakeholders in a series of 11 sessions. Overall, more than three hundred community leaders representing more than 140 organizations and institutions participated in the consultation, which gave them an opportunity to provide input on priorities and orientations for the Secrétariat.

Rapport de la tournée de consultation 2019 : Construire des ponts : Tournée de consultation menée en 2019, auprès des organismes qui servent les communautés d’expression anglaise, sur les priorités et les orientations du Secrétariat aux relations avec les Québécois d’expression anglaise - Ravensbergen, Frances (Secrétariat aux relations avec les Québécois d’expression anglaise (SRQEA), 2020)
À l’automne 2019, le Secrétariat aux relations avec les Québécois d’expression anglaise a entrepris une série de onze séances de consultation auprès d’intervenantes et intervenants communautaires et institutionnels. En tout, plus de trois cents dirigeantes et dirigeants communautaires, qui représentaient au-delà de cent quarante organisations et institutions, ont participé à des activités de consultation dans le but de commenter les priorités et les orientations du Secrétariat.

4Korners Activities - 4 Korners Family Resource Center (2020)

4Korners Activities - 4 Korners Family Resource Center (2020)

Annual Report 2019-2020 - Community Health and Social Services Network (CHSSN) (2020)

Rapport annual 2019-2020 - Community Health and Social Services Network (CHSSN) (2020)

4Korners Activities - 4 Korners Family Resource Center (2020)

4Korners Activities - 4 Korners Family Resource Center (2020)

4Korners Activities - 4 Korners Family Resource Center (2020)

4Korners Activities - 4 Korners Family Resource Center (2020)

4Korners Activities ONLINE - 4 Korners Family Resource Center (2020)

Caregivers' Guide : Local and Regional Resources for Caregivers in the Centre-du-Québec - Centre for Access to Services in English (CASE) (2020)
The Institut de la Statistique du Québec states that as of 2015 as many as a quarter of the population of Québec were caregivers, the majority being female, for people with long-term health complications. The recipient of the care is most often a family member. The reason for needing care varies between chronic illness, disability, and difficulties related to aging. Of those providing care to family members, greater than one third act as a caregiver to more than one person.

4Korners Activities ONLINE - 4 Korners Family Resource Center (2020)

4Korners April 2020 - 4 Korners Family Resource Center (2020)

One Voice Coalition - Farrow, Anna; Wong, Judy (2020)

Annual Report 2020-2021 - Community Health and Social Services Network (CHSSN) (2020)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2020)

Community NetLink - Community Health and Social Services Network (CHSSN) (2020)

Partners for Better Care - Community Health and Social Services Network (CHSSN) (2020)
Keywords: Official Language Minority Community (OLMC)

Adapting Services During the Pandemic : The Example of Jeffery Hale-Saint Brigid's and Its Partners - Duchesne, Anne (2020)

Making a Difference in the Laurentians - LESAN (2020)

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 - Pocock, Joanne (Community Health and Social Services Network, 2020)
The Baseline Data Report 2019-2020 (BDR) is the eighteenth volume of a series produced by the Community Health and Social Services Network (CHSSN) to serve as a relevant and comprehensive knowledge base regarding the situation of Québec’s English-speaking population in the area of health. The Baseline Data Report series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de l'Est-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de l'Estrie-CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de l'Ouest-de-l'Île de Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English language Health and Social Services in Québec : RTS de l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de la Gaspésie - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de la Montérégie-Centre - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de Lanaudière - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS du Centre Ouest de l'Île de Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS du Centre Sud de l'Île de Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS du Nord de l'Île de Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Access Programs for Health and Social Services in the English Language : Presentation to NPIs - Prata, Ghislaine (2019)

Baseline Data Report 2018-2019 Part 1 (Telephone Survey) : English-language Health and Social Services Access in Québec - Pocock, Joanne (Community Health and Social Services Network, 2019)
The Baseline Data Report series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2018-2019 explores a single factor that is a key determinant of the health of English-speaking Quebec, namely, access to health and social services.

Baseline Data Report 2018-2019 Part 2 (Focus Groups) : English-language Health and Social Services Access in Québec - Pocock, Joanne (Community Health and Social Services Network, 2019)
The CHSSN focus groups were designed as face-to-face group discussions with a lead moderator. As the accompanying table indicates, nine focus groups were held across six regions with a total attendance of 116 English speakers (18+). The recruitment process entailed a public announcement by the host organizations located in each region: Neighbours Regional Association of Rouyn-Noranda (NRARN), English Community Organization in Saguenay-Lac-St-Jean (ECO-02), North Shore Community Association (NSCA), Coasters Association (Coasters), Megantic Community Development Corporation (MCDC), and the Centre for Access to Services in English (CASE). The host organizations in each region also assumed responsibility for arranging a time, finding a location, providing refreshments and technical assistance.

English-speaking Quebecers Shows High Levels of Distrust with Coalition Avenir Québec Government - Quebec Community Groups Network (QCGN) (2019)

Annual Report 2018-2019 - Community Health and Social Services Network (CHSSN) (2019)

August 2019 4K Newsletter - 4 Korners Family Resource Center (2019)

English-speaking fathers in Quebec exposed to greater vulnerability - Community Health and Social Services Network (CHSSN) (2019)

June 2019 4K Newsletter - 4 Korners Family Resource Center (2019)

May 2019 4K Newsletter - 4 Korners Family Resource Center (2019)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2019)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2019)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2019)

QCGN Begs to Differ on Premier's Interpretation of English Signage in Hospitals - Quebec Community Groups Network (QCGN) (2019)

LAURENTIANS 4K NEWSLETTER - 4 Korners Family Resource Center (2019)

Survey on Access to Health Care and Social Services for the English-speaking Community of Laval - AGAPE (2019)

Community Health Education Program (CHEP) 2018-2019 - Community Health and Social Services Network (CHSSN) (2019)
The CHSSN Community Health Education Program (CHEP) serves the urban, rural and remote English-speaking communities around the province of Quebec, providing health and social information and support via video conferencing through the RUIS (McGill) Telehealth system. Twenty community NPI networks funded under the CHSSN Network Partner Initiative (NPI) from across the province of Quebec participated, by attending the CHEP video conferences and by hosting a CHEP DVD viewing session. The following report highlights the Community Health Education Program (CHEP) activities for the period from April 1, 2018, to March 31, 2019.

Community NetLink - Community Health and Social Services Network (CHSSN) (2019)

Community NetLink - Community Health and Social Services Network (CHSSN) (2019)

Vitality - Community Health and Social Services Network (CHSSN) (2019)
Keywords: Official Language Minority Community (OLMC)

Who We Are - Community Health and Social Services Network (CHSSN) (2019)

Who Are Our 0-5 year Olds? : A Portrait of English-speaking 0-5 Year Olds in the Outaouais Region WHO AREOER - Connexions Resource Centre (2019)

Community Mobilization Model for Improving the Health and Vitality of English-Speaking Communities in Quebec - Kueber, Russell (Community Health and Social Services Network (CHSSN), 2019)
This brief description of a "Community Mobilization Model for Improving the Health and Vitality of English-speaking Communities in Quebec" includes a condensed background of English-speaking communities. It also includes a short description of some key concepts used in the model. The model is designed to communicate the approach taken by community helath and social services networks, which positions them as drivers of change in mobilizing English-speaking communities.

Promoting the Health and Well-being of English Speaking Seniors in Quebec : A Community Model - Kueber, Russell; Pocock, Joanne; Hobbs-Robert, Jennifer; Hale, Jeffery (Community Health and Social Services Network (CHSSN), 2019)
This document describes a community model for improving the health and well-being of a linguistic minority senior population in Quebec. English-speaking seniors have unique challenges due to language barriers, socioeconomic inequalities as well as the lack of awareness of their needs and lack of representation associated with the minority status of their community. Many community organizations have recognized the critical level of vulnerability of this population and have designed and implemented successful strategies to address these challenges while remaining aligned with the Quebec government's comprehensive strategies and approaches on healthy aging such as Vieillir et vivre ensemble and Municipalite amie des aines. The main purpose of the document is to help inform and guide English-speaking communities and their community and public partners in their ongoing collaborative efforts to effectively adapt programs and services to improve the lives of English-speaking seniors in their communities.

Community-based Process Results in Strong Watchdog Committee for English Health and Social Services - Quebec Community Groups Network (QCGN) (2018)

Long Awaited Regulation Creating Provincial Access to Committee a First Step in the Right Direction - Quebec Community Groups Network (QCGN) (2018)

Network News - Quebec Community Groups Network (QCGN) (2018)

Improving Access to Health and Social Services and Information in the English Language - Prata, Ghislaine (2018)

Adaptation Initiative Project Guide 2014-2018 - Community Health and Social Services Network (CHSSN) (2018)
The CHSSN’s initiative to adapt health and social services is supported by an investment from Health Canada, through the Roadmap for Canada's Official Languages 2013–2018: Education, Immigration, Communities. This initiative is being undertaken in partnership with the Ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded in order to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English. The agreement also divided the roles and responsibilities among the CHSSN, the MSSS, and the health and social services agencies.

Adaptation Initiative Project Guide 2018-2023 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

Adaption Gaspésie-Les-Îles 2014-2018 : Improved Access to Inter-Regional Health and Social Services for the English-speaking Population of Gaspésie-Îles-de-la-Madeleine - Community Health and Social Services Network (CHSSN) (2018)

Annual Report 2017-2018 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

Investment Priorities 2013-2018 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

L'initiative d'adaptation : guide des projets 2018-2023 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

Regional Priorities : QCGN Members 2018 - Quebec Community Groups Network (QCGN) (2018)
This document is a collaborative effort on the part of the regional member organization's of Quebec Community Groups Network to ensure regional priorities are at the fore of the Priority Setting Steering Committee discussions and to establish preferred and inclusive methods of consultation among regional member groups.

News from the Evidence Base : Findings from the 2016 Census of Canada - Pocock, Joanne (2017)
Keywords: Official Language Minority Community (OLMC)

A Website Created to Support English-speaking Patients from Eastern Regions in Quebec Traveling Away from Home for Medical Services - Community Health and Social Services Network (CHSSN) (2017)

A Needs Assessment : Better Understanding the Current Situation of the Senior Population - Burke, Helena; Craig, Lisa; Richardson, Mary (Council for Magdalen Islanders (CAMI), 2017)
This needs assessment was conducted as part of a community development process in the English-speaking community of Grosse-Ile, on the Magdalen Islands, Quebec. It is part of the follow- up to a community portrait that was developed through a participatory process in early 2015. The process involved the mobilization and engagement of a number of local stakeholders as well as community residents who expressed their views on a number of different themes. One of the issues that was highlighted by community members as a concern, even a priority, was that of the aging population within the ESC, having access to few services and limited support for caregivers.
Keywords: Official Language Minority Community (OLMC)

Une évaluation des besoins : mieux comprendre la situation actuelle des aînés - Burke, Helena; Craig, Lisa; Richardson, Mary (Council for Magdalen Islanders (CAMI), 2017)
Cette évaluation des besoins a été menée dans le cadre d’un processus de développement communautaire dans la communauté anglophone de Grosse-Île, aux Îles-de-la-Madeleine, Québec. Elle fait partie du suivi d’un portrait communautaire qui a été élaboré par le biais d’un processus participatif au début de 2015. Le processus a impliqué la mobilisation et l’engagement de plusieurs intervenants locaux ainsi que de résidents de la communauté qui ont exprimé leurs opinions sur un bon nombre de thèmes. L’un des enjeux qui a été souligné par les membres de la communauté comme une préoccupation, voire une priorité, était celui du vieillissement de la population au sein de la CAI, ayant peu de services et un soutien limité aux proches aidants.
Keywords: Official Language Minority Community (OLMC)

Health Passport : When Language Matters / Passport santé : Question de langue - Assistance and Referral Centre (ARC) (2017)

Building Together : Succesful Partnerships Between Community and the Health and Social Services System - Community Health and Social Services Network (CHSSN) (2017)
The Community Health and Social Services Network (CHSSN) coordinates a Quebec-wide health and social services “Adaptation Program” designed to enhance the vitality of English-speaking minority communities in Quebec by increasing access to existing health and social services for Englishspeaking Quebecers. The program is supported by an investment from Health Canada and has been undertaken in partnership with the ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English through partnerships between local English-speaking communities and health and social services system.
Keywords: Official Language Minority Community (OLMC)

Mobilizing / se Mobilisent - Community Health and Social Services Network (CHSSN) (2017)

Dialogue : Better Communication for Better Care - Dialogue McGill (2017)

Dialogue : Mieux communiquer pour mieux soigner - Dialogue McGill (2017)

Demographic Summaries for English-speaking Populations Across Quebec's RTS Territories (2011) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
This document contains a series of one-page summaries highlighting the key demographic characteristics of the English-speaking populations for each of the new health territories established by the MSSS in 2015 as part of the re-organization of health services. The 25 health geographies in this series are the RTS which is the French-language acronym for the Réseau territoriale des services which correspond to the CISSS and CIUSSS territories. This series is intended as a knowledge resource for the CHSSN NPI networks.

2015 CHSSN-CROP Survey on Community Vitality : Findings on English-speaking Community Vitality Across Key Sectors - Pocock, Joanne (Community Health and Social Services Network, 2016)
This 2015-2016 Baseline Data Report relays key findings of the 2015 CHSSN/CROP Survey on Community Vitality as they unfold across key sectors. The commonalities and distinct features of regional communities within the English-speaking provincial population are delineated as well as sub-groups defined by gender, age, household income and level of bilingualism. This report from the 2015 survey is intended as a companion to the 2015-2016 Baseline Data Report entitled English Language Access to Health and Social Services in Québec, which includes a summary of results from Focus Group sessions conducted in several regions around the province.

Baseline Data Report 2015-2016 : English-language Health and Social Services Access in Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
This 2015-2016 Baseline Data Report relays the health and social service findings of the 2015 CHSSN/CROP Survey on Community Vitality. The commonalities and distinct features of regional communities within the English-speaking provincial population are delineated as well as sub-groups defined by gender, age, household income, health status and level of bilingualism. While this report is limited to the health and social service sector, the Survey on Community Vitality (2005, 2010, and 2015) also collects the opinions, perceptions and expectations of a representative sample of English-speaking Quebecers in most regions of Quebec with respect to issues in education, human resource development, justice, culture and communications. The 2015 study replicates previous surveys conducted by CROP in 2000 for the Missisquoi Institute and again in 2005 and 2010 for the CHSSN.
Keywords: Official Language Minority Community (OLMC)

Programme d’accès : aux services de santé et aux services sociaux en langue anglaise pour les personnes d’expression anglaise de la Capitale-Nationale : 2012-2015 - Laroche, Daniel; Blais, Sébasitien; Paquette, Brigitte (Centre intégré universitaire de santé et de services sociaux de la Capitale Nationale, 2016)
En décembre 2015, le ministère de la Santé et des Services sociaux (MSSS) demandait au Centre intégré universitaire de santé et de service sociaux de la Capitale-Nationale de procéder à une mise à jour du Programme d’accès aux services de santé et aux services sociaux en langue anglaise pour les personnes d’expression anglaise 2012-2015 (programme d’accès) de leur région respective. Le dernier programme d’accès élaboré par l’Agence de la santé et des services sociaux de la Capitale- Nationale avait fait l’objet d’une approbation par le Ministère en 2012. La démarche de mise à jour vise un portrait actuel des services de santé et des services sociaux en langue anglaise considérant le contexte actuel de la réorganisation du réseau de la santé et des services sociaux entamé depuis l’adoption de la LMRSSS, Loi modifiant l’organisation et la gouvernance du réseau de la santé et des services sociaux notamment par l’abolition des agences régionales.

Trousse : Vous devez vous déplacer pour des soins de santé? - Committee for Anglophone Social Action (CASA); Council for Anglophone Magdalen Islanders (CAMI); Vision Gaspé-Percé Now; Centre integré de santé et de services sociaux de la Gaspésie (2016)

English-language Interpretation Services to Improve Language Access to Health and Social Services for Members of English-speaking Communities in Quebec : Status Report - Kosseim, Myléne (Community Health and Social Services Network (CHSSN), 2016)
This study aims to document the current situation regarding the use of formal interpreters as a means of language access to health and social services for English-speaking persons and to propose possible improvements to the Ministère de la Santé et des Services sociaux.
Keywords: Official Language Minority Community (OLMC)

McGill Program Networks Creating Impacts - Buffitt, Kimberly (2015)

Accès interrégional aux services sociaux et de santé pour les personnes d'expression anglaise de l'est de Québec - Richardson, Mary (2015)
Keywords: Official Language Minority Community (OLMC)

Inter-regional Access to Specialized Health and Social Services for English-speakers from Eastern Quebec - Richardson, Mary (2015)
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Characteristics of Visible Minorities in Quebec's English-speaking Communities - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2015)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for xyz. The variables covered are: - Gender - Age structure - Household living arrangements - Recent mobility - Educational attainment - Labour force activity - Income - Low-income cut-off

Inter-Regional Access to Specialized Health and Social Services for English-speakers from Eastern Quebec - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This project was developed to better understand the experience and needs of English speakers from the eastern regions of Quebec (Gaspésie - Îles-de-la-Madeleine, the North Shore, including the Lower North Shore, and the Lower Saint-Lawrence) as concerns extra-regional health and social services. The specific challenges facing this official language minority community were known only anecdotally, but needed to be better understood before effective action could be taken to address the needs of this population.
Keywords: Official Language Minority Community (OLMC)

Mental Health Resource Guide for the Gaspé Coast and Magdalen Islands - Dow, Cynthia; Harrison, Kim; Payette, Tom; Synnott, Jessica (2015)

The Policy on Language of Service - Jeffery Hale - Saint Brigid's (JHSB) (2015)
The objective of this policy is to ensure that employees communicate effectively with both French and English‐speaking clients and that Language Assistance Services are also available for other Limited‐French or English Proficient (LFEP) individuals and their surrogate decision‐makers at all points of contact, in a timely fashion and in their preferred language in order to ensure an understanding of their health condition and treatment options.

Canadian Community Health Survey (2011-2012) : Findings Related to the Mental and Emotional Health of Quebec's English-speaking Communities - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2015)
This report is organized around two primary objectives. The first objective is to provide reliable knowledge regarding the mental and emotional health of Quebec’s English-speaking minority communities. In so doing, this report contributes up-to-date and relevant findings to the evidence base that informs the decision-making and initiatives of organizations serving this population. This objective is served by 131 statistical tables and descriptive commentary that provide information drawn from the 2011-2012 Canadian Community Health Survey (CCHS). The second objective is to consult the body of experience and expertise of community organizations and networks many of whom are on the front-line in meeting the needs and building the resiliency of English speakers in this aspect of their health and well-being. This objective has been met by soliciting the response of five organizations to the picture of the situation among English speakers conveyed by the CCHS tabulations. As a panel, the organizations were invited to address how this knowledge might serve as a resource in setting priorities and designing initiatives benefitting English-speaking communities. In other words, as a tool in developing community capacity.
Keywords: Official Language Minority Community (OLMC)

Language Access Policy : Planning & Implementation Guide - Prata, Ghislaine (Jeffery Hale - Saint Brigids (JHSB), 2015)
Jeffery Hale – Saint Brigid’s (JHSB) is a public, bilingual institution under participatory governance dedicated to providing safe, compassionate and high quality care. Among the strategic objectives of the organisation are the promotion of linguistic duality and openness to cultural diversity. Recognizing that language access is an integral component of the delivery of high quality and safe health services, JHSB has developed a number of policies, procedures and tools in the area of linguistic access. The organisation is currently seeking to consolidate and develop these initiatives within the framework of a comprehensive language access policy. This report provides a theoretical model and reference to practical tools to inform organisational efforts in the development of a language access policy and the implementation and continuous improvement of a language access plan.
Keywords: Official Language Minority Community (OLMC)

Îles-de-la-Madeleine : Portrait de la communauté d'expression anglaise - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
Le présent portrait a été réalisé en collaboration avec de nombreux partenaires locaux, à l’initiative du Conseil des anglophones madelinots (CAMI) et avec l’appui du Réseau communautaire de santé et de services sociaux (RCSSS). Parmi les autres groupes ayant participé au processus figurent la Municipalité de Grosse-Île, l’école de Grosse-Île, la Corporation d’employabilité et de développement économique communautaire (CEDEC), le Centre scolaire communautaire (CSC) et l’Agglomération des Îles (comité de développement social/Les Îles en Forme).

Portrait of the English-speaking Community of Rouyn-Noranda - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This portrait has been completed by Neighbours and the Community Health and Social Services Network (CHSSN), in collaboration with the Centre intégré de santé et des services sociaux (CISSS), the city of Rouyn-Noranda (Villes et villages en santé) and the local English school, Noranda School. Neighbours is a non-profit community organization established to serve the Englishspeaking population of the Rouyn-Noranda area through facilitating information sharing, defending the right of access to service in English and organizing social and cultural events. Neighbours is committed to strengthening networks within the English and French speaking population as well as encouraging community development initiatives. The main objective of this portrait is to contribute to a more in-depth understanding of the English-speaking community of Rouyn-Noranda in order to address the issues it faces.
Keywords: Official Language Minority Community (OLMC)

Portrait of the English-speaking Community of the Magdalen Islands - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This portrait has been completed in collaboration with many local partners, through the initiative of the Council for Anglophone Magdalen Islanders (CAMI), with support from the Community Health and Social Services Network (CHSSN). Other groups involved in this process include the municipality of Grosse-Ile, the Grosse-Ile school, the Community Economic Development and Employability Corporation (CEDEC), the Community Learning Centre (CLC), Agglomération des Îles (social development committee/Les Îles en Forme).

Community Vitality Survey of the English-speaking Community of Quebec - Community Health and Social Services Network (CHSSN) (2015)

Blazing a Trail for Active and Healthy Aging: An Action Plan for Quebec’s English-speaking Seniors 2010-2015 / Tracer la voie pour vieillir en santé et demeurer actif : Plan d’action à l’intention des aînés d’expression anglaise du Québec 2010-2015 - Quebec Community Groups Network (QCGN) (2015)

The English-speaking Population of des Collines-de-l'Outaouais : a Community Portrait - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This portrait has been completed by Connexions and the Community Health and Social Services Network (CHSSN), in collaboration with the Centre intégré de santé et de services sociaux des Collines de l’Outaouais (CISSSO). Connexions (the Connexions Resource Centre) is a not-for-profit community organization whose mission is to serve and promote the health, well-being and vitality of the English-speaking population of the Outaouais. It is committed to strengthening networks within the English and French speaking population as well as encouraging community development initiatives.

Letter of Support for QCGN - Zucchi, John (2014)

[Letter re: Bill 10 - Letters of Support of QCGN] - Committee for Anglophone Social Action (CASA); Coasters Association; Community Health and Social Services Network (CHSSN); Jeffery Hale - Saint Brigid's (JHSB); Neighbours Regional Association of Rouyn-Noranda; Quebec Community Groups Network (QCGN); Quebec Federation of Home and School Associations (QFHSA) (2014)

[Letter Regarding Bill 10 from QCGN President] - DePoe, Lawrence (2014)

Mémoire du Quebec Community Groups Network déposé à la Commission de la santé et des services sociaux de l’Assemblée nationale du Québec : Le projet de loi n° 10, loi visant à modifier l’organisation et la gouvernance du réseau de la santé et des services sociaux, notamment par l’abolition des agences régionales - Quebec Community Groups Network (QCGN) (2014)

Retention Program for the McGill University Training and Retention of Health Professionals Project : Evaluation of the retention program measure and recommendations - Gagnon, Marie-Pierre (Dialogue McGill, 2014)
This report presents an evaluation of the activities implemented under the Retention Program, in relation to the Support for Health and Social Services Institutions and Support for Educational Institutions in order to highlight the main strengths and areas for improvement. The mandate was to identify strategies that could help to increase the impact of the internship program on the retention of health and social services professionals in the health and social services network. The evaluation would then contribute to the ongoing improvement of this program, by providing some direction to guide the actions of those responsible for the McGill University Training and Retention of Health Professionals Project and project partners.

Long Live Healthy Development Framework - Buffitt, Kimberly (2014)
Keywords: Official Language Minority Community (OLMC)

Recovery Support Program : A Community Wellness Program for English-speaking People with Mental Illness - Jeffery Hale - Saint Brigid's (JHSB) (2014)

Brief Submitted to La commission de la santé et des services sociaux de l'Assemblée nationale du Québec Concerning Bill 10, An Act to Modify the Organization of the Health and Social Services Network, in Particular by Abolishing the Regional Agencies - Quebec Community Groups Network (QCGN) (2014)

Community Portrait : St. Léonard - Richardson, Mary; Jobson, Shirley (Community Health and Social Services Network (CHSSN), 2013)
In 2009, the Community Health and Social Services Network (CHSSN) concluded an agreement with Quebec’s Institut national de santé publique (INSPQ) to develop knowledge on the English-speaking population of Quebec as part of a program concerning health projects for official language minority communities. Gaining a better understanding of English-speaking communities in Quebec is one of the objectives of that collaboration, and it is explored here through the lens of community development.

Community Portrait : Laval - Richardson, Mary; Jobson, Shirley (Community Health and Social Services Network (CHSSN), 2013)
In 2009, the Community Health and Social Services Network (CHSSN) concluded an agreement with Quebec’s Institut national de santé publique (INSPQ) to develop knowledge on the English-speaking population of Quebec as part of a program concerning health projects for official language minority communities. Gaining a better understanding of English-speaking communities in Quebec is one of the objectives of that collaboration, and it is explored here through the lens of community development.
Keywords: Official Language Minority Community (OLMC)

Baseline Data Report 2012-2013 : Quebec's English-speaking Community Networks and their Partners in Public Health and Social Services - Pocock, Joanne (Community Health and Social Services Network, 2013)
The 2012-2013 BDR reports unpon the nature and development of the partnerships that CHSSN Networking and Partnership Initiative (NPI) networks have established in their regions. The report represents the experience, thoughts, and observations - the collective wisdom - of the NPI networks on a range of topics related to their partnerships. The report looks back at the work incolved in partnering since the genesis of CHSSN, the ongoing challenges and successes, and the perceived impact of partnering on the NPI communities and their access to health and social services in English.
Keywords: Official Language Minority Community (OLMC)

Improving Access to Health and Social Services for Quebec’s English-speaking Population : Development Priorities 2013-2018 - Udy, Michael; Howarth, Kelly; Kischuk, Nathalie; Medeiros, CMA (Community Health and Social Services Network (CHSSN), 2013)
This report has been prepared at the request of the Community Health and Social Services Network (CHSSN). It is intended for presentation to Health Canada in the context of the renewal of the Federal Government’s commitments to official language minority communities (OLMCs) for the period 2013-2018. The report presents development priorities for the improvement of access to health and social services in English for Quebec’s English-speaking communities as identified by the personnel of organizations work- ing on this issue.

Improving Access to Health and Social Services for Quebec’s English-speaking Population: Development Priorities 2013-2018 : A Companion Document - Udy, Michael; Howarth, Kelly; Kischuk, Nathalie; Medeiros, CMA (Community Health and Social Services Network (CHSSN), 2013)
This document has been prepared at the request of the Community Health and Social Service Network (CHSSN). It is the companion document to Improving Access to Health and Social Services for Quebec’s English- Speaking Population, Development Priorities 2013-2018, also prepared at the request of the CHSSN. Both are intended for presentation to Health Canada in the context of the renewal of the Federal Government’s com- mitments to official linguistic minorities for the period 2013-2018. These commitments have been funded to date under the Roadmap for Canada’s Linguistic Duality 2008-2013 (the Roadmap). More about the context of the project is presented in Appendix I.

Community Portrait : Sept-Îles - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2012)
In 2009, the Community Health and Social Services Network (CHSSN) concluded an agreement with Quebec’s Institut national de santé publique (INSPQ) to develop knowledge on the English-speaking population of Quebec as part of a program concerning health projects for official language minority communities. Gaining a better understanding of English-speaking communities in Quebec is one of the objectives of that collaboration, and it is explored here through the lens of community development.

Declaration from the Community Priority Setting Conference of the English-Speaking Community of Quebec - Quebec Community Groups Network (QCGN) (2012)

Programme d’accès aux services de santé et aux services sociaux en langue anglaise pour les personnes d’expression anglaise : 2012-2015 - Labrecque, Edith; Paquette, Brigitte (Jeffery Hale - Saint Brigid's (JHSB), 2012)
En novembre 2010, le ministère de la Santé et des Services sociaux (MSSS) demandait aux agences de procéder à la révision du programme d’accès aux services de santé et aux services sociaux en langue anglaise pour les personnes d’expression anglaise de leur région respective. Le dernier programme d’accès, élaboré par l’Agence de la santé et des services sociaux de la Capitale-Nationale, avait été approuvé par ce même ministère en décembre 2007. Conformément à la loi, ces programmes doivent être révisés tous les trois ans, ce qui implique la mise en place d’une démarche permettant d’assurer leur actualisation. Ce travail permet donc de revoir la situation prévalant actuellement dans la région à l’intention de la population d’expression anglaise, d’apporter les bonifications nécessaires afin de mieux répondre à leurs besoins, et ce, en matière d’accessibilité, de continuité, de complémentarité et de qualité dans les services offerts. Il implique nécessairement un grand nombre de partenaires provenant de divers établissements de la région.

Baseline Data Report 2011-2012 : Socio-Economic Profiles of the English-speaking Visible Minority Population by Quebec Health Region - Pocock, Joanne (Community Health and Social Services Network, 2012)
The Baseline Data Report series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well being of their constituencies.
Keywords: Official Language Minority Community (OLMC)

Baseline Data Report 2011-2012 : Socio-Economic Profiles of the English-speaking Visible Minority Population by Quebec Health Region - Pocock, Joanne (Community Health and Social Services Network, 2012)
The Baseline Data Report series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well being of their constituencies.
Keywords: Official Language Minority Community (OLMC)

Access to Health and Social Services : A Comparison of French & English-language CROP-CHSSN Survey Samples - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2011)
The Baseline Data Report (BDR) is a report developed to serve as a resource that will allow NPI communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well being of their constituencies. There is now a series of inter‐related Baseline Data Reports (see below) which may be accessed through the CHSSN website (www.chssn.org).
Keywords: Official Language Minority Community (OLMC)

Baseline Data Report 2010-2011 : English-language Health and Social Services Access in Quebec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2011)
The 2010-2011 Baseline Data Report relays the health and social service findings of the 2010 CHSSN-CROP Survey on Community Vitality Survey and compares them with the findings of the 2005 survey. In order to facilitate the five year comparison the design of the present report reproduces, as much as possible, that of the 2005-2006 BDR. The commonalities and distinct features of regional communities within the English-speaking provincial population are delineated as well as sub-groups defined by gender, age, household income, health status and level of bilingualism. While this report is limited to the health and social service sector, the Survey on Community Vitality also collects the opinions, perceptions and expectations of a representative sample of English-speaking Quebecers in each region of Quebec with respect to issues in education, manpower development, culture and communications. The 2010 study replicates a previous survey conducted by CROP in 2000 for the Missisquoi Institute and again in 2005 for the CHSSN. A survey was also done among a representative sample of French-speaking Quebecers on the same issues. These results are not presented in this report.
Keywords: Official Language Minority Community (OLMC)

Brief : Submitted to the Federal Parliamentary Committee on Palliative and Compassionate Care by the English-speaking Catholic Council - The English Speaking Catholic Council (ESCC) (2010)
The English Speaking Catholic Council acknowledges with deep gratitude the invaluable contribution of the principal authors of this brief: Dr. Ramona Coelho, a family physician who works at CLSC Metro in Montreal. Her training included a focus in palliative care. She spends half of her practice caring for disabled and frail elderly persons who are homebound. And Daniel Cere, Ph.D., Professor, Faculty of Religious Studies, McGill University, and member of the Board of the ESCC. The English Speaking Catholic Council is pleased to present this Brief to the Federal Parliamentary Committee on Palliative and Compassionate Care.

Training and Human Resources Development Project : Final Report - Dialogue McGill (2010)
McGill University’s 2004-2008 Training and Human Resources Development Project sought to contribute to improving English-speaking Quebecers’ access in their own language to the range of health and social services offered to the general population. The 2004-2008 Project was funded through Health Canada’s program to support Quebec initiatives for improving access to health care and social services for English speakers. It was sponsored by McGill University’s Faculty of Arts and administered by its English and French Language Center in conjunction with its School of Social Work. The budget allocated for the 2004- 2008 period was $ 11,757,828. The project had two objectives: to ensure effective communication between English-speakers and the health and social services workers serving them and to increase the participation of English-speaking professionals in the Quebec health and social services network.

Coasters Association Inc. Presentation to the Standing Senate Committee on Official Languages - Coasters Association (2010)
The Lower North Shore, with a total population of less than six thousand, consists of fourteen (14) isolated communities, twelve predominantly English speaking, two Francophone communities, and two Montagnais reserves (Five municipalities.) These communities are spread over 550 km on the North East coast of Quebec.
Keywords: Official Language Minority Community (OLMC)

Baseline Data Report 2009-2010 : Demographic Profiles of Quebec's English-speaking Communities by selected CSSS Territories - Pocock, Joanne; Warnke, Jan (Community Health and Social Services Network (CHSSN), 2010)
This document presents selected demographic characteristics of the English-speaking population of the CSSS territories in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI) of the Community Health and Social Services Network (CHSSN). The information presented is drawn from the 2006 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec's official language minoritty community.
Keywords: Official Language Minority Community (OLMC)

Projet de formation et de développement des ressources humaines : Rapport annuel - Dialogue McGill (2009)
The McGill Training and Human Resource Development Project contributes to other Quebec government initiatives aimed at ensuring that English-speaking people in Quebec enjoy equitable access, in their own language, to the full range of health and social services available to the general population. Its two main objectives are to ensure effective communication in English between English-speaking Quebecers and the health and social services workers who serve their needs and to increase the number of English-speaking professionals working in the Quebec health and social services system. The Project involves the implementation of four measures in partnership with stakeholders concerned by the issue of access to health and social services in the English-speaking communities. The 2008-2009 year was an extension of the Project which finished in March 2008.

Training and Human Resources Development Project : Annual Report - Dialogue McGill (2009)
The McGill Training and Human Resource Development Project contributes to other Quebec government initiatives aimed at ensuring that English-speaking people in Quebec enjoy equitable access, in their own language, to the full range of health and social services available to the general population. Its two main objectives are to ensure effective communication in English between English-speaking Quebecers and the health and social services workers who serve their needs and to increase the number of English-speaking professionals working in the Quebec health and social services system. The Project involves the implementation of four measures in partnership with stakeholders concerned by the issue of access to health and social services in the English-speaking communities. The 2008-2009 year was an extension of the Project which finished in March 2008.

Baseline Data Report 2008-2009 : Regional Profiles of Quebec's English-speaking Communities Selected 1996-2006 Census Findings - Pocock, Joanne; Warnke, Jan (Community Health and Social Services Network (CHSSN), 2009)
The Baseline Data Report 2009 uses 2006 census information to provide Quebec’s Englishspeaking regional communities with a view of their current position with respect to selected health determinants and, where possible, change and continuity since the census findings of 1996. It is the first report in the series of Baseline Data Reports produced since 2004 to situate these communities in an evolving ten year trend.
Keywords: Official Language Minority Community (OLMC)

Delivering Health and Social Services in English to English-speakers in the Capitale-Nationale Region (CNR) Revised Access Program: 2006-2009 : Translated and Edited Version - Jeffery Hale - Saint Brigid's (JHSB) (2008)
To comply with the latter, the Capitale-Nationale Region's Health and Social Services Network Development Agency (CNR Agency) launched a review of the health and social services offered in English to English speakers in the region.

Executive Summary of the Document "Delivering Health and Social services in English to English-speakers in the Capitale-Nationale Region (CNR) Revised Access Program: 2006-2009" - Jeffery Hale - Saint Brigid's (JHSB) (2008)
Between June and November 2006, the Agency Responsible for Health and Social Services in Québec's Capitale-Nationale region (or the CNR Agency) prepared a comprehensive Access Program report. This document details how health and social services are delivered in English to English speakers in the greater Quebec City region.

Questions and Answers about Access to Health and Social Services in English in the Capitale-Nationale Region (CNR) - Jeffery Hale - Saint Brigid's (JHSB) (2008)

Training and Human Resources Development Project : Annual Report - Dialogue McGill (2008)
The McGill Training and Human Resource Development Project contributes to other Quebec government initiatives aimed at ensuring that English-speaking people in Quebec enjoy equitable access, in their own language, to the full range of health and social services available to the general population. Its two main objectives are to ensure effective communication in English between English-speaking Quebecers and the health and social services workers who serve their needs and to increase the number of English-speaking professionals working in the Quebec health and social services system. The Project involves the implementation of four measures in partnership with stakeholders concerned by the issue of access to health and social services in the English-speaking communities. The 2008-2009 year was an extension of the Project which finished in March 2008.

The Baseline Data Report 2007-2008 : Quebec's Social and Health Survey Information - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2008)
The Health and Social Services Networking and Partnership Initiative (HSSNPI) is a funding program of the Quebec Community Groups Network mandated by Health Canada as a measure of the Federal Action Plan for Official Language Communities. The HSSNPI aims to support the creation of durable links and joint action between English-speaking communities and Quebec’s health and social services system. The Baseline Data Report is a series produced by the Community Health and Social Services Network (CHSSN) to serve as a relevant and comprehensive knowledge base regarding the health status and vitality of Quebec’s English‐speaking population. The report is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders to develop strategies to improve the well‐being of their constituencies.
Keywords: Official Language Minority Community (OLMC)

Training and Human Resources Development Project : Annual Report - Dialogue McGill (2007)
The McGill Training and Human Resource Development Project contributes to other Quebec government initiatives aimed at ensuring that English-speaking people in Quebec enjoy equitable access, in their own language, to the full range of health and social services available to the general population. Its two main objectives are to ensure effective communication in English between English-speaking Quebecers and the health and social services workers who serve their needs and to increase the number of English-speaking professionals working in the Quebec health and social services system. The Project involves the implementation of four measures in partnership with stakeholders concerned by the issue of access to health and social services in the English-speaking communities. The 2008-2009 year was an extension of the Project which finished in March 2008.

The Baseline Data Report 2006-2007 - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2007)
In 2002, the Community Health and Social Services Network (CHSSN) was a key Contributor to the report of the Consultative Committee for English‐speaking Minority Communities to the Federal Minister of Health.1 The Consultative Committee report proposed a five year Global Intervention Plan to support the English‐speaking communities’ efforts to improve access to health and social services in their language in Quebec. The Consultative Committee emphasized that improved access was intimately tied to the ability of English‐speaking communities to develop local networks and effective partnerships with public sector agencies. It was proposed that by maintaining and improving English‐language access to a full range of health and social services across diverse regional populations that these partnerships would help to promote better health outcomes and ensure the vitality of Quebec’s English‐speaking communities. The Committee underlined the need to pay special attention to the more isolated and demographically weak communities which face special challenges in providing health and social services in English to their respective populations.
Keywords: Official Language Minority Community (OLMC)

Project Report : Community Health and Social Services Network (CHSSN) : Community Radio : January 1 to March 31, 2007 - Howarth, Kelly; Kueber, Russell (Community Health and Social Services Network (CHSSN), 2007)
The findings and processes were to be documented and shared with the Lower North Shore (local radio station and regional English-speaking organization, COASTERs Association). In addition, consultation and support was to be given to both service providers to increase their capacity to better serve the English-speaking regions in the future.

Social Support Networks in Quebec's English-speaking Communities : Building Community Vitality Through Social Capital Strategies - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2006)
This report arises in response to one of the objectives of the “We Can Act” project sponsored by the Community Health and Social Services Network (CHSSN). The CHSSN is a network of 60 community resources, associations, foundations, public institutions and other stakeholders dedicated to the development of partnerships in health and social services for English‐speaking communities in Quebec. The CHSSN promotes knowledge‐based community development as a means for communities to enhance their vitality and improve the health and well‐being of their members. Consistent with the population health approach, CHSSN sponsors projects and partnerships which address health determinants affecting the health status of communities as well as supportive strategies to attain a sustainable health and social service system.
Keywords: Official Language Minority Community (OLMC)

A Study of Women's Needs on the Lower North Shore - Keats, Shannon A. (Coasters Association, 2006)
The mission of the Coasters Association is to develop knowledge of the needs and expectations of the fourteen (14) communities on the Lower North Shore, and act in partnership with community leaders, organizations and stakeholders to design and deliver community strategies, programs and services which respond to the region’s development challenges. In keeping with their mission and providing an opportunity to better the situation of women on the Lower North Shore, a project entitled “A Study of the Needs of Women on the Lower North Shore”, was initiated. The project began on the September 12th, 2005 and ended on March 31st, 2006 (29 weeks). The key goal of the project was to get women involved and talk about the issues facing them and to identify opportunities and lasting solutions, as well as make women aware of the programs and services that are available on the coast, through partnerships with other organizations and to help these women make use of those programs. The purpose of the project was to research information through means of a questionnaire and by organizing focus groups to develop a needs assessment and to establish a coalition (for Phase 2 of the project) to improve the overall status of women on the Lower North Shore of Quebec.

Rapport de Données de Base 2005-2006 : Accés aux services de santé et aux services sociaux en anglais au Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2006)
Keywords: Official Language Minority Community (OLMC)

The Baseline Data Report 2005-2006 : English-language Health and Social Services Access in Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2006)
Keywords: Official Language Minority Community (OLMC)

Brief on Building Local Health and Social Services Networks in Montreal - Allmand, Warren (English Speaking Catholic Council, 2004)
The ESCC was formed in 1980 as a focal point for coordinating community activities among English-speaking Roman Catholics in Montreal and later across all Quebec. In keeping with the mission of the Church and with its teachings on the role of the laity in the modern world, the English Speaking Catholic Council acts in the fields of education, health and social services, social justice and culture to build a sense of community identity and common purpose. We encourage the development of leadership in the community and assist in coordinating human resources in community-based institutions and we endeavour to ensure effective representation before government bodies and on various boards, committees and councils.

Mémoire du Conseil catholique d’expression anglaise sur la création de réseaux locaux de services de santé et de services sociaux à Montréal - Allmand, Warren (Conseil catholique d’expression anglaise, 2004)

Baseline Data Report 2003-2004 : Regional Profiles of English-speaking Communities - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2004)
This report includes a general overview of the situation of the English‐speaking population in a minority context as well as the particular demographic characteristics and vitality issues which vary tremendously across its 16 administrative health regions • The profile of each region is organized to highlight a broad range of factors that have been shown to have a strong influence on the health status of a population and ultimately the quality of life of its constituents • These health determinants are located in the context of national, provincial and regional demographic characteristics with comparisons between Anglophone minority and Francophone majority populations within a regional territory • Where significant, and possible, the tendencies of certain factors over time will be underlined • The commonalities among English‐speaking regional communities as well as the distinct features of each in terms of demographics, experiences, and attitudes are highlighted throughout this process and summarized in terms of key strengths and needs to be targeted in considering future health and social service initiatives
Keywords: Official Language Minority Community (OLMC)

Choices through Knowledge: Community training in palliative care - Jones, Jo-Ann; Quebec Association for Adult Learning (QAAL) (2004)

Population Health Initiative : A Community Guide to the Population Health Approach - Community Health and Social Services Network (CHSSN) (2003)

Alliance Quebec Will Take Action if PQ Reduces Guarentees of Access to English Health Services - Alliance Quebec (AQ) (2001)

AQ Requests Meeting with Premier Landry - Alliance Quebec (AQ) (2001)

Brief to the Estates General on the French Language - Alliance Quebec (AQ) (2001)
In 1982, following its long tradition of creating organizations and institutions to meet its needs and fulfill its aspirations, the English-speaking community created Alliance Quebec to respond to the dramatic changes in Quebec's society. Alliance Quebec is a non-profit, volunteer-based, community organization committed to the preservation and enhancement of the English-speaking communities and it's institutions in Quebec. Alliance Quebec serves as voice on public policy for the English-speaking communities. To that end, we strive for acceptance of an open and multicultural society; a commitment to a united Canada; a participative and integrated approach toward community retention and development; and proactive and entrepreneurial management.

Brief Presented to la commission des états généraux sur la situation et l'avenir de la langue française au Québec - The English Speaking Catholic Council (ESCC) (2001)
The English Speaking Catholic Council is a registered non-profit organization, made up of men and women from both the public and private sectors – all volunteers – who come together with a commitment to support and speak on behalf of their community in the fields of social justice, education, health and social services, and culture. In this year 2001, designated by the United Nations as the “International Year of Dialogue Among Civilizations”, the English Speaking Catholic Council comes before the Estates General with the hope of stimulating greater dialogue and understanding in a spirit of mutual respect among all people in Quebec.

Communication and Efficiency : Language and Health Care Brief Presented to the Clair Commission - Alliance Quebec (AQ) (2001)
Alliance Quebec welcomes the opportunity to present the concerns of the English-speaking community during the public consultations on the reorganization of health care. As we all know, communication is fundamental to proper diagnosis and treatment of the patient. It also plays a vital role in ensuring a patient is comfortable with his or her health care professional. Alliance Quebec is of the opinion that no matter how fine and efficient a health care system is, it will be less effective if it cannot communicate effectively with the patient and vice versa.

Mémoire à la Commission d'étude sur les services de santé et les services sociaux - Alliance Quebec (AQ) (2001)
Alliance Québec est heureuse d'avoir l'occasion d'exposer les préoccupations de la collectivité d'expression anglaise pendant les consultations publiques sur la réorganisation des soins de santé.

Making Quebec Health Care User-Friendly (Again) - Hamelin, Michael J.; Bechervaise, Lynden; Goodwin, Robina; King, Maurice; Buckle, Scott; May, Bob; Jackson, Léon (2001)

The Ontario Government Should Fully Respect the Province's French-speaking Minority: AQ - Alliance Quebec (AQ) (2000)

Justice for English-speaking Quebecers - Alliance Quebec (AQ) (1999)

Adoption of Seven Health and Social Services Access Plans : Too Little Too Late - Alliance Quebec (AQ) (1999)

Statement by William Johnson, President of Alliance Quebec in Reply to an Attack by Gary Richards, President of the Townshippers' Association - Johnson, William (1999)

Alliance Quebec Goes At Last to Court to Force the Government to Approve Long Overdue English Health Services - Alliance Quebec (AQ) (1999)

Statement by Alliance Quebec President William Johnson on Applying for a Writ of Mandamus to Force the Quebec Government to Approve Access Plans to English Health and Social Services - Alliance Quebec (AQ) (1999)

Newsletter - The Centre for Literacy of Quebec (CFL) (1999)

[Letter from William Johnson, President of Alliance Quebec, to Hon. Lucien Bouchard, Premier of Quebec] - Johnson, William (1998)

An Outlaw Government - Alliance Quebec (AQ) (1998)

Alliance Quebec Demands that People Receive Health and Social Services in the Language They Choose to Use - Alliance Quebec (AQ) (1997)

Le discours de Lucien Bouchard au Centaur - Un an plus tard, un bilan - Alliance Quebec (AQ) (1997)

The Centaur Speech - One Year Later - Alliance Quebec (AQ) (1997)

Alliance-Quebec Condemns Language Bureaucrats' Involvement in Health Care - Alliance Quebec (AQ) (1997)

Alliance Quebec Petitions Information Commission for Answers on OLF Health Report - Alliance Quebec (AQ) (1997)

Alliance Québec réclame que les gens reçoivent des services sociaux et de santé dans la langue de leur choix - Alliance Quebec (AQ) (1997)

Alliance Québec : Une nouvelle étude sur la langue vise-t-elle les institutions anglophones et les gens qui y travaillent? - Alliance Quebec (AQ) (1996)

Coasters Association Informer - Coasters Association (1994)

Working Papers on English Language Institutions in Quebec - Schachter, Susan (Alliance Quebec (AQ), 1982)
This project was designed to provide a resource for Quebec's English-speaking community and others who feel the need for information about themselves and those institutions usually identified as "English". The decision that such a resource was needed was based on both objective and subjective criteria. Objectively, the English-speaking population of Quebec is, and always has been, an unstable one; that is, large numbers of English-speaking people have always been among those moving to and from the province, Ieaving behind a relatively small core of their fellows with deep roots in Quebec. This high turn-over in population has affected the continuity of the English-speaking community. Such a state of fluidity has made it difficult to evolve a distinctive English-speaking cultural identity with Quebec as its focal point. On the other hand, it has Ied to a discontinuity in the knowledge of our economic, political and cultural role in Quebec. Hence, the need for a resource such as this.

Good Communication : the Key to Quality Health Care - Centre for Access to Services in English (CASE)
First Nations and Inuit, immigrants and refugees, the deaf, or official language speakers in minority situations, such as English in Québec, or French speakers in the rest of Canada, can face language barriers. Even for bilingual people, linguistic barriers might arise in a health care situation due to stress levels, complex or unusual vocabulary, cultural differences, or physical factors associated with the illness itself.

Travelling for Health? Toolkit - Committee for Anglophone Social Action (CASA) (Vision Gaspé-Percé Now)
The goal for this TOOLKIT is to provide English-speakers, from the Gaspé Coast and the Magdalen Islands, helpful information when they must travel out‑of‑region for health services. A Steering Committee, which included CASA, CAMI, VPGN and the CISSS de la Gaspésie, oversaw the development of this project with support from Jeffrey Hale Community Partners (JHCP).

Health Profile of English-speaking Minority Communities in Quebec - Community Health and Social Services Network (CHSSN)
Keywords: Official Language Minority Community (OLMC)

Use it or Lose it - Neighbours Regional Association of Rouyn-Noranda

Aller de l'avant : Renforcer les capacités de recherche en lien avec les aînés d’expression anglaise du Québec - Quebec Community Groups Network (QCGN)
La population canadienne vieillit plus rapidement aujourd’hui que jamais auparavant. En 2011, on estime que cinq millions de Canadiens étaient âgés de 65 ans et plus. On s’attend à ce que ce chiffre double d’ici à 22-25 ans pour atteindre 10,4 millions en 2036. Ici au Québec, les défis et les opportunités de la population vieillissante sont amplifiés. En 2011, près de 1,3 million de personnes vivant au Québec étaient âgées de 65 ans et plus. Parmi ces derniers, environ 160 000 étaient âgés de 85 ans et plus. Comme les baby-boomers (nés entre 1946 et 1966) continuent à vieillir, on estime que le nombre de personnes âgées de 65 ans et plus augmentera de 16 % de la population en 2011 à 26 % en 2031. Ceci représente un million de personnes âgées additionnel au Québec d’ici aux 30 prochaines années.
Keywords: Official Language Minority Community (OLMC)

Building a New Bridge of understanding and discovery of the English-speaking Community of the Monteregie Centre (South Shore) - Richardson, Mary (Assistance and Referral Centre)

Literacy Across the Curriculumedia Focus - The Centre for Literacy of Quebec (CFL)

Literacy Across the Curriculumedia Focus - The Centre for Literacy of Quebec (CFL)

Brief to the Romanow Royal Commission on the Future of Health Care in Canada - The English Speaking Catholic Council (ESCC)
The English Speaking Catholic Council welcomes the opportunity to present its perspective and its recommendations to the Commission on the Future of Health Care in Canada. We bring to the task great respect for the efforts of Mr. Romanow and his team and a firm conviction that the Commissioner is correct when he writes in his Interim Report that “the Medicare house needs remodeling but not demolishing.”

Services Available for Seniors in the Gaspé-Barachois Area - Vision Gaspé-Percé Now (VGPN)